Self-compacting concrete using waste residue as raw material and preparation method thereof

By modifying the waste slag and adding lanthanum oxide/carbon composite materials and mullite fibers, the problem that existing self-finished concrete is difficult to utilize solid waste slag when using a large amount of river sand is solved, and the improvement of high strength, toughness and corrosion resistance is achieved. .

CN116283149BActive Publication Date: 2025-02-25JIANGSU JINHAINING NEW BUILDING MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310290372.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-23
Publication Date
2025-02-25
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

The existing self-finished concrete is difficult to effectively utilize solid waste slag when using a large amount of river sand, and its strength, toughness and corrosion resistance are insufficient.

Method used

Modified waste residue is used as the main fine aggregate, and the modified waste residue is treated with aqueous formic acid and maleic anhydride solution to improve its dispersion performance and binding force in concrete. At the same time, lanthanum oxide/carbon composite materials and mullite fibers are added to enhance the strength, toughness and corrosion resistance of the concrete.

Benefits of technology

Under the conditions of large amounts of waste slag, concrete has high strength, high toughness, good corrosion resistance and excellent construction performance, and significantly improves the overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004141205450000111
    Figure BDA0004141205450000111
  • Figure BDA0004141205450000121
    Figure BDA0004141205450000121
  • Figure BDA0004141205450000122
    Figure BDA0004141205450000122
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and in particular to a self-compacting concrete using waste slag as a raw material and a preparation method thereof. The self-compacting concrete comprises the following raw materials in parts by weight: 100 parts of silicate cement, 115-145 parts of modified waste slag, 65-85 parts of river sand, 230-260 parts of crushed stone, 2.6-3.7 parts of lanthanum oxide / carbon composite material, 1.2-1.5 parts of mullite fiber, 2.3-4.2 parts of EVA emulsion, 3-6 parts of silica fume, 0.3-0.6 parts of water reducer and 45-53 parts of water. The concrete prepared by the invention has high strength and high toughness, good corrosion resistance, strong construction performance and excellent comprehensive performance when a large amount of waste slag is used as a raw material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a self-compacting concrete using waste slag as raw material and a preparation method thereof. Background Art

[0002] In recent years, due to the shortage of construction sand resources, river sand is currently the most commonly used construction sand. However, long-term over-exploitation of river sand has caused adverse effects on the environment. Therefore, the high-value utilization of solid waste residue has important application value in concrete.

[0003] Self-compacting concrete refers to concrete that can flow and compact under its own gravity, can completely fill the formwork even with dense steel bars, and has good homogeneity and does not require additional vibration. Self-compacting concrete is increasingly widely used because it has the advantages of ensuring good compaction of concrete, improving production efficiency, reducing equipment wear, increasing the freedom of structural design, and improving the working environment.

[0004] The domestic patent with application number CN202211311908.5 discloses a C60 high-performance self-compacting concrete suitable for arch structures, including the following components by weight: 445-460 parts of cement, 55-57 parts of fly ash, 55-57 parts of mineral powder, 750-780 parts of fine aggregate, 940-970 parts of coarse aggregate, 18-22 parts of steel fiber, 10.2-10.5 parts of dispersant, 8.3-8.6 parts of water reducer, and 158 parts of water. The fine aggregate used in the self-compacting concrete is medium sand in zone II, which accounts for a large proportion of the concrete, and at the same time, not much waste slag is used. Therefore, the development of a self-compacting concrete with waste slag as the main fine aggregate has a good role in promoting the high-value utilization of solid waste slag. Summary of the invention

[0005] The purpose of the present invention is to provide a self-compacting concrete using waste slag as raw material and a preparation method thereof. The prepared concrete has high strength and toughness, good corrosion resistance, strong construction performance and excellent comprehensive performance when using a large amount of waste slag as raw material.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0007] A self-compacting concrete using waste residue as raw material comprises the following raw materials in parts by weight: 100 parts of silicate cement, 115-145 parts of modified waste residue, 65-85 parts of river sand, 230-260 parts of crushed stone, 2.6-3.7 parts of lanthanum oxide / carbon composite material, 1.2-1.5 parts of mullite fiber, 2.3-4.2 parts of EVA emulsion, 3-6 parts of silica fume, 0.3-0.6 parts of water reducer and 45-53 parts of water.

[0008] Preferably, the modified waste residue is prepared by the following method:

[0009] (1) mixing iron tailings, gold tailings, and building stone tailings uniformly to obtain mixed waste slag;

[0010] (2) placing the mixed waste residue in a formic acid aqueous solution so that the formic acid aqueous solution submerges the mixed waste residue, then heating the mixture to 50-55° C. with stirring, and then filtering the mixture to obtain pretreated mixed waste residue;

[0011] (3) placing the pretreated mixed waste residue and the maleic anhydride aqueous solution in a tank body so that the maleic anhydride aqueous solution can immerse the pretreated mixed waste residue, then sealing the tank body, and raising the temperature inside the tank body to 70-75° C., after standing, opening the tank body and filtering to obtain the modified waste residue.

[0012] Preferably, in step (1), the mass ratio of the iron tailings, gold tailings, and building stone tailings is 10:(2-6):(1-3);

[0013] The fineness modulus of the iron tailings is 0.8-1.3; the fineness modulus of the gold tailings is 0.5-0.7; the particle size of the building stone tailings is 0.2-3mm, and the stone powder content is 15-25%.

[0014] Preferably, in step (2), the mass fraction of the formic acid aqueous solution is 2-3%; and the stirring time is 30-50 min.

[0015] Preferably, in step (3), the mass fraction of the maleic anhydride aqueous solution is 0.3-0.5%, and the standing time is 60-80 min.

[0016] Preferably, the lanthanum oxide / carbon composite material is prepared by the following method:

[0017] 1) adding lanthanum nitrate hexahydrate, polyvinyl pyrrolidone, polyethylene glycol and trimesic acid to a mixed solvent to obtain a mixed solution; placing the mixed solution in a reaction kettle, then sealing the reaction kettle, placing it in an oven, then heating it to 150-170° C. for solvent thermal reaction for 10-12 hours, then cooling it to room temperature, opening the reaction kettle, centrifugally washing the material in the kettle, and then vacuum drying it to obtain a solid intermediate product; 2) grinding the solid intermediate product and passing it through a 100-150 mesh sieve, then heating it to 260-280° C. in an argon atmosphere, keeping it warm for 30-50 minutes, then heating it to 760-800° C. in an argon atmosphere, keeping it warm for 70-100 minutes, then cooling it to room temperature in an argon atmosphere, grinding it and passing it through a 200-300 mesh sieve to obtain a lanthanum oxide / carbon composite material.

[0018] Preferably, in step 1), the mass ratio of the mixed solvent, lanthanum nitrate hexahydrate, polyvinyl pyrrolidone, polyethylene glycol and trimesic acid is (500-600):(1-1.5):(16-24):(3-5):(2.5-4); the mixed solvent is prepared by mixing water, ethanol and N,N-dimethylformamide in a volume ratio of 1:(2-3):(1-2);

[0019] The number average molecular weight of the polyvinyl pyrrolidone is 50000-80000; the polyethylene glycol is polyethylene glycol 400 or polyethylene glycol 600.

[0020] Preferably, in step 2), the temperature is increased to 260-280°C at a rate of 2-3.5°C / min; and the temperature is increased to 760-800°C at a rate of 4.5-7°C / min.

[0021] Preferably, the silicate cement is P.II52.5 silicate cement;

[0022] The river sand is medium sand in zone II, with a fineness modulus of 2.4-2.8;

[0023] The crushed stone is a continuous grade crushed stone with a particle size of 5-20 mm;

[0024] The diameter of the mullite fiber is in the range of 100-500 μm, and the aspect ratio is 8-15;

[0025] The solid content of the EVA emulsion is 65-70%;

[0026] The silica content of the silica fume is more than 90%, and the specific surface area is 17000-20000m 2 / kg;

[0027] The water reducing agent is a powdered polycarboxylate water reducing agent.

[0028] As a general inventive concept, the present invention provides a method for preparing self-compacting concrete using waste slag as raw material, comprising the following steps:

[0029] Step 1: Add EVA emulsion to the modified waste residue and stir for 10-15 minutes, then add river sand and stir evenly, then add lanthanum oxide / carbon composite material and stir evenly, then add mullite fiber and silica fume in sequence, stir evenly, and obtain a mixture;

[0030] Step 2: Add the mixture to the silicate cement, stir evenly, then add 2 / 3-4 / 5 of the formula amount of water, stir for 100-130 seconds, then add the remaining raw materials, stir evenly to obtain the self-compacting concrete.

[0031] The technical effects of the present invention are:

[0032] 1. The present invention adopts modified waste slag as the main fine aggregate, which can effectively reduce the use of river sand, reduce the comprehensive cost of concrete, and can comprehensively utilize abandoned iron tailings, gold tailings, and building stone tailings to achieve high-value utilization of difficult-to-dispose waste slag.

[0033] The modified waste residue in the present invention is first pretreated with formic acid to change the surface activity of the waste residue, and then treated with an aqueous solution of maleic anhydride to obtain maleic anhydride-modified waste residue. The modified waste residue has good dispersibility in concrete and has a higher binding force with other components, thereby improving the strength and other properties of the concrete.

[0034] At the same time, when modifying the waste slag, the present invention reasonably configures the mixing ratio of iron tailings sand, gold tailings sand and building stone tailings, and reasonably controls the particle size of each waste slag, so that the particle size distribution of the waste slag is excellent and better meets the working requirements of concrete.

[0035] 2. The present invention adds lanthanum oxide / carbon composite material to self-compacting concrete, which has good dispersion performance. In the lanthanum oxide / carbon composite material, lanthanum oxide is dispersed and fixed on the carbon nanomaterial with high bonding strength, forming more anchor points on the carbon material, which can make it easier for the carbon nanomaterial and the gel material to be tightly combined and more firmly embedded in the concrete. It can also reduce micro cracks in the concrete, strengthen the weak areas of the concrete, improve the density of the concrete, and effectively enhance the strength and toughness of the concrete.

[0036] In addition, the lanthanum oxide / carbon composite material of the present invention can effectively improve the corrosion resistance of self-compacting concrete, has good resistance to chloride ion penetration, and can enhance the fluidity and water retention of concrete, making it easier to cast and form, and having better construction performance.

[0037] 3. The present invention adds an appropriate amount of mullite fiber to the self-compacting concrete, which can bridge the cracks in the concrete and reduce the generation of cracks in the concrete. In addition, the mullite fiber can form a certain connection with the lanthanum oxide / carbon composite material in the concrete, forming a network structure of point-line combination in the concrete, further enhancing the toughness and strength of the concrete.

[0038] 4. The present invention adds an appropriate amount of EVA emulsion to the concrete, which can enhance the structural stability of the modified waste slag on the one hand, thereby better exerting the role of fine aggregate, and on the other hand strengthen the bonding force of various raw materials, thereby improving the strength and crack resistance of concrete.

[0039] 5. The present invention reasonably configures various raw materials so that the prepared concrete has high strength and toughness, good corrosion resistance, strong construction performance and excellent comprehensive performance when using a large amount of waste slag as raw materials. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Embodiment 1:

[0042] A lanthanum oxide / carbon composite material is prepared by the following method:

[0043] 1) Add lanthanum nitrate hexahydrate, polyvinyl pyrrolidone (number average molecular weight of 50,000), polyethylene glycol 600 and trimesic acid into a mixed solvent to obtain a mixed solution; the mass ratio of the mixed solvent, lanthanum nitrate hexahydrate, polyvinyl pyrrolidone, polyethylene glycol and trimesic acid is 600:1.2:22:5:2.5; the mixed solvent is prepared by mixing water, ethanol and N,N-dimethylformamide in a volume ratio of 1:2:2.

[0044] The mixed liquid is placed in a reactor, which is then sealed and placed in an oven. The temperature is then raised to 165°C for a solvent thermal reaction for 12 hours. The reactor is then cooled to room temperature, the reactor is opened, the material in the reactor is centrifuged and washed, and then vacuum dried to obtain a solid intermediate product.

[0045] 2) The solid intermediate product was ground and passed through a 150-mesh sieve, and then heated to 260°C at a rate of 3°C / min in an argon atmosphere, kept warm for 50 min, and then heated to 780°C at a rate of 4.5°C / min, kept warm for 100 min, and then cooled to room temperature in an argon atmosphere, ground and passed through a 240-mesh sieve to obtain a lanthanum oxide / carbon composite material.

[0046] Embodiment 2:

[0047] A lanthanum oxide / carbon composite material is prepared by the following method:

[0048] 1) Add lanthanum nitrate hexahydrate, polyvinyl pyrrolidone (number average molecular weight of 50,000), polyethylene glycol 400 and trimesic acid into a mixed solvent to obtain a mixed solution; the mass ratio of the mixed solvent, lanthanum nitrate hexahydrate, polyvinyl pyrrolidone, polyethylene glycol and trimesic acid is 550:1.5:16:4:3; the mixed solvent is prepared by mixing water, ethanol and N,N-dimethylformamide in a volume ratio of 1:3:1.

[0049] The mixed liquid is placed in a reactor, which is then sealed and placed in an oven. The temperature is then raised to 170°C for a solvent thermal reaction for 12 hours. The reactor is then cooled to room temperature, the reactor is opened, the material in the reactor is centrifugally washed, and then vacuum dried to obtain a solid intermediate product.

[0050] 2) The solid intermediate product was ground and passed through a 150-mesh sieve, and then heated to 270°C at a rate of 3.5°C / min in an argon atmosphere, kept warm for 45 minutes, and then heated to 800°C at a rate of 4.5°C / min, kept warm for 70 minutes, and then cooled to room temperature in an argon atmosphere, ground and passed through a 300-mesh sieve to obtain a lanthanum oxide / carbon composite material.

[0051] Embodiment 3:

[0052] A lanthanum oxide / carbon composite material is prepared by the following method:

[0053] 1) Add lanthanum nitrate hexahydrate, polyvinyl pyrrolidone (number average molecular weight of 80,000), polyethylene glycol 600 and trimesic acid into a mixed solvent to obtain a mixed solution; the mass ratio of the mixed solvent, lanthanum nitrate hexahydrate, polyvinyl pyrrolidone, polyethylene glycol and trimesic acid is 500:1:24:5:4; the mixed solvent is prepared by mixing water, ethanol and N,N-dimethylformamide in a volume ratio of 1:2:2.

[0054] The mixed liquid is placed in a reactor, which is then sealed and placed in an oven. The temperature is then raised to 150° C. for a solvent thermal reaction for 10 hours. The reactor is then cooled to room temperature, the reactor is opened, the material in the reactor is centrifuged and washed, and then vacuum dried to obtain a solid intermediate product.

[0055] 2) The solid intermediate product is ground and passed through a 100-mesh sieve, and then heated to 260°C at a rate of 2°C / min in an argon atmosphere, kept warm for 30 minutes, and then heated to 800°C at a rate of 7°C / min, kept warm for 70 minutes, and then cooled to room temperature in an argon atmosphere, ground and passed through a 200-mesh sieve to obtain a lanthanum oxide / carbon composite material.

[0056] Embodiment 4:

[0057] A lanthanum oxide / carbon composite material is prepared by the following method:

[0058] 1) Add lanthanum nitrate hexahydrate, polyvinyl pyrrolidone (number average molecular weight of 80,000), polyethylene glycol 400 and trimesic acid into a mixed solvent to obtain a mixed solution; the mass ratio of the mixed solvent, lanthanum nitrate hexahydrate, polyvinyl pyrrolidone, polyethylene glycol and trimesic acid is 550:1.2:20:3:2.5; the mixed solvent is prepared by mixing water, ethanol and N,N-dimethylformamide in a volume ratio of 1:2:1.

[0059] The mixed liquid is placed in a reactor, which is then sealed and placed in an oven. The temperature is then raised to 170°C for a solvent thermal reaction for 11 hours. The reactor is then cooled to room temperature, the reactor is opened, the material in the reactor is centrifugally washed, and then vacuum dried to obtain a solid intermediate product.

[0060] 2) The solid intermediate product was ground and passed through a 100-mesh sieve, and then heated to 280°C at a rate of 3°C / min in an argon atmosphere, kept warm for 45 minutes, and then heated to 760°C at a rate of 6°C / min, kept warm for 100 minutes, and then cooled to room temperature in an argon atmosphere, ground and passed through a 200-mesh sieve to obtain a lanthanum oxide / carbon composite material.

[0061] Embodiment 5:

[0062] A self-compacting concrete using waste residue as raw material comprises the following raw materials in parts by weight: 100 parts of P.Ⅱ52.5 silicate cement, 125 parts of modified waste residue, 75 parts of river sand, 240 parts of crushed stone, 3.2 parts of lanthanum oxide / carbon composite material, 1.3 parts of mullite fiber, 4 parts of EVA emulsion, 6 parts of silica fume, 0.6 parts of powdered polycarboxylate water reducer and 49 parts of water.

[0063] The river sand is medium sand in zone II, with a fineness modulus of 2.8; the crushed stone is a continuous grade crushed stone with a particle size of 5-20 mm; the diameter of the mullite fiber ranges from 100-500 μm, and the aspect ratio is 8-15; the solid content of the EVA emulsion is 65-70%; the silica content of the silica fume is greater than 90%, and the specific surface area is 17000 m 2 / kg. The lanthanum oxide / carbon composite material was prepared by the method in Example 1.

[0064] The modified waste residue is prepared by the following method:

[0065] (1) Iron tailings, gold tailings and building stone tailings are mixed evenly to obtain mixed waste slag; the mass ratio of iron tailings, gold tailings and building stone tailings is 10:5:3; the fineness modulus of iron tailings is 1.3; the fineness modulus of gold tailings is 0.5; the particle size of building stone tailings is 0.2-3 mm, and the stone powder content is 21%.

[0066] (2) placing the mixed waste residue in a 3% by mass formic acid aqueous solution, allowing the formic acid aqueous solution to immerse the mixed waste residue, then heating the mixture to 55° C. and stirring for 30 minutes, and then filtering the mixture to obtain the pretreated mixed waste residue.

[0067] (3) The pretreated mixed waste residue and a 0.5% by mass maleic anhydride aqueous solution are placed in a tank body so that the maleic anhydride aqueous solution can immerse the pretreated mixed waste residue. The tank body is then sealed and the temperature inside the tank body is raised to 70° C. After standing for 80 minutes, the tank body is opened and filtered to obtain the modified waste residue.

[0068] The method for preparing the self-compacting concrete using waste slag as raw material comprises the following steps:

[0069] Step 1: Add EVA emulsion to the modified waste residue and stir for 15 minutes, then add river sand and stir evenly, then add lanthanum oxide / carbon composite material and stir evenly, then add mullite fiber and silica fume in sequence, stir evenly, and obtain a mixture;

[0070] Step 2: Add the mixture to P.Ⅱ52.5 silicate cement, stir evenly, then add 4 / 5 of the formula amount of water, stir for 115 seconds, then add the remaining raw materials, stir evenly to obtain the above-mentioned self-compacting concrete.

[0071] Embodiment 6:

[0072] A self-compacting concrete using waste residue as raw material comprises the following raw materials in parts by weight: 100 parts of P.Ⅱ52.5 silicate cement, 115 parts of modified waste residue, 85 parts of river sand, 235 parts of crushed stone, 3.5 parts of lanthanum oxide / carbon composite material, 1.5 parts of mullite fiber, 3.5 parts of EVA emulsion, 5 parts of silica fume, 0.5 parts of powdered polycarboxylate water reducer and 53 parts of water.

[0073] The river sand is medium sand in zone II, with a fineness modulus of 2.4; the crushed stone is a continuous grade crushed stone with a particle size of 5-20 mm; the diameter of the mullite fiber ranges from 100 to 500 μm, and the aspect ratio is 8-15; the solid content of the EVA emulsion is 70%; the silica content of the silica fume is greater than 90%, and the specific surface area is 20,000 m 2 / kg. The lanthanum oxide / carbon composite material was prepared by the method in Example 3.

[0074] The modified waste residue is prepared by the following method:

[0075] (1) Iron tailings, gold tailings and building stone tailings are mixed evenly to obtain mixed waste slag; the mass ratio of iron tailings, gold tailings and building stone tailings is 10:6:1; the fineness modulus of iron tailings is 0.8; the fineness modulus of gold tailings is 0.7; the particle size of building stone tailings is 0.2-3 mm, and the stone powder content is 21%.

[0076] (2) placing the mixed waste residue in a 3% by mass formic acid aqueous solution, allowing the formic acid aqueous solution to immerse the mixed waste residue, then heating the mixture to 50° C. and stirring for 35 minutes, and then filtering the mixture to obtain the pretreated mixed waste residue.

[0077] (3) The pretreated mixed waste residue and a 0.4% by mass maleic anhydride aqueous solution are placed in a tank body so that the maleic anhydride aqueous solution can immerse the pretreated mixed waste residue. The tank body is then sealed and the temperature inside the tank body is raised to 70° C. After standing for 80 minutes, the tank body is opened and filtered to obtain the modified waste residue.

[0078] The method for preparing the self-compacting concrete using waste slag as raw material comprises the following steps:

[0079] Step 1: Add EVA emulsion to the modified waste residue and stir for 10 minutes, then add river sand and stir evenly, then add lanthanum oxide / carbon composite material and stir evenly, then add mullite fiber and silica fume in sequence, stir evenly, and obtain a mixture;

[0080] Step 2: Add the mixture to P.Ⅱ52.5 silicate cement, stir evenly, then add 4 / 5 of the formula amount of water, stir for 100s, then add the remaining raw materials, stir evenly to obtain the above-mentioned self-compacting concrete.

[0081] Embodiment 7:

[0082] A self-compacting concrete using waste residue as raw material comprises the following raw materials in parts by weight: 100 parts of P.Ⅱ52.5 silicate cement, 145 parts of modified waste residue, 70 parts of river sand, 255 parts of crushed stone, 2.6 parts of lanthanum oxide / carbon composite material, 1.3 parts of mullite fiber, 2.9 parts of EVA emulsion, 5 parts of silica fume, 0.3 parts of powdered polycarboxylate water reducer and 50 parts of water.

[0083] The river sand is medium sand in zone II, with a fineness modulus of 2.8; the crushed stone is a continuous grade crushed stone with a particle size of 5-20 mm; the diameter of the mullite fiber ranges from 100 to 500 μm, and the aspect ratio is 8-15; the solid content of the EVA emulsion is 65%; the silica content of the silica fume is greater than 90%, and the specific surface area is 17000 m 2 / kg. The lanthanum oxide / carbon composite material was prepared by the method in Example 4.

[0084] The modified waste residue is prepared by the following method:

[0085] (1) Iron tailings, gold tailings and building stone tailings are mixed evenly to obtain mixed waste slag; the mass ratio of iron tailings, gold tailings and building stone tailings is 10:2:1; the fineness modulus of iron tailings is 0.8; the fineness modulus of gold tailings is 0.5; the particle size of the building stone tailings is 0.2-3 mm, and the stone powder content is 21%.

[0086] (2) placing the mixed waste residue in a 2% by mass formic acid aqueous solution, allowing the formic acid aqueous solution to immerse the mixed waste residue, then heating the mixture to 55° C. and stirring for 50 minutes, and then filtering the mixture to obtain the pretreated mixed waste residue.

[0087] (3) The pretreated mixed waste residue and a 0.3% by mass maleic anhydride aqueous solution are placed in a tank body so that the maleic anhydride aqueous solution can immerse the pretreated mixed waste residue. The tank body is then sealed and the temperature inside the tank body is raised to 75° C. After standing for 60 minutes, the tank body is opened and filtered to obtain the modified waste residue.

[0088] The method for preparing the self-compacting concrete using waste slag as raw material comprises the following steps:

[0089] Step 1: Add EVA emulsion to the modified waste residue and stir for 13 minutes, then add river sand and stir evenly, then add lanthanum oxide / carbon composite material and stir evenly, then add mullite fiber and silica fume in sequence, stir evenly, and obtain a mixture;

[0090] Step 2: Add the mixture to P.Ⅱ52.5 silicate cement, stir evenly, then add 2 / 3 of the formula amount of water, stir for 130 seconds, then add the remaining raw materials, stir evenly to obtain the above-mentioned self-compacting concrete.

[0091] Embodiment 8:

[0092] A self-compacting concrete using waste residue as raw material comprises the following raw materials in parts by weight: 100 parts of P.Ⅱ52.5 silicate cement, 115 parts of modified waste residue, 75 parts of river sand, 240 parts of crushed stone, 2.9 parts of lanthanum oxide / carbon composite material, 1.5 parts of mullite fiber, 4.2 parts of EVA emulsion, 4.5 parts of silica fume, 0.3 parts of powdered polycarboxylate water reducer and 45 parts of water.

[0093] The river sand is medium sand in zone II, with a fineness modulus of 2.4; the crushed stone is a continuous grade crushed stone with a particle size of 5-20 mm; the diameter of the mullite fiber ranges from 100 to 500 μm, and the aspect ratio is 8-15; the solid content of the EVA emulsion is 70%; the silica content of the silica fume is greater than 90%, and the specific surface area is 20,000 m 2 / kg. The lanthanum oxide / carbon composite material was prepared by the method in Example 2.

[0094] The preparation method of the modified waste residue is the same as that of Example 5. The preparation method of the self-compacting concrete using the waste residue as raw material is the same as that of Example 5.

[0095] Embodiment 9:

[0096] A self-compacting concrete using waste residue as raw material comprises the following raw materials in parts by weight: 100 parts of P.Ⅱ52.5 silicate cement, 145 parts of modified waste residue, 85 parts of river sand, 260 parts of crushed stone, 3.5 parts of lanthanum oxide / carbon composite material, 1.5 parts of mullite fiber, 4 parts of EVA emulsion, 6 parts of silica fume, 0.3 parts of powdered polycarboxylate water reducer and 53 parts of water.

[0097] The river sand is medium sand in zone II, with a fineness modulus of 2.5; the crushed stone is a continuous grade crushed stone with a particle size of 5-20 mm; the diameter of the mullite fiber ranges from 100-500 μm, and the aspect ratio is 8-15; the solid content of the EVA emulsion is 70%; the silica content of the silica fume is greater than 90%, and the specific surface area is 17000 m 2 / kg. The lanthanum oxide / carbon composite material was prepared by the method in Example 1.

[0098] The preparation method of the modified waste residue is the same as that of Example 7. The preparation method of the self-compacting concrete using the waste residue as raw material is the same as that of Example 5.

[0099] Embodiment 10:

[0100] A self-compacting concrete using waste residue as raw material comprises the following raw materials in parts by weight: 100 parts of P.Ⅱ52.5 silicate cement, 122 parts of modified waste residue, 65 parts of river sand, 230 parts of crushed stone, 3.7 parts of lanthanum oxide / carbon composite material, 1.2 parts of mullite fiber, 2.3 parts of EVA emulsion, 3 parts of silica fume, 0.6 parts of powdered polycarboxylate water reducer and 51 parts of water.

[0101] The river sand is medium sand in zone II, with a fineness modulus of 2.8; the crushed stone is a continuous grade crushed stone with a particle size of 5-20 mm; the diameter of the mullite fiber ranges from 100 to 500 μm, and the aspect ratio is 8-15; the solid content of the EVA emulsion is 65%; the silica content of the silica fume is greater than 90%, and the specific surface area is 20,000 m 2 / kg. The lanthanum oxide / carbon composite material was prepared by the method in Example 3.

[0102] The preparation method of the modified waste residue is the same as that of Example 6. The preparation method of the self-compacting concrete using the waste residue as raw material is the same as that of Example 7.

[0103] Comparative Example 1:

[0104] A self-compacting concrete using waste slag as raw material, which is different from Example 5 in that the modified waste slag is replaced by mixed waste slag, and the mixed waste slag is made by mixing iron tailings, gold tailings, and building stone tailings in a mass ratio of 10:5:3.

[0105] Comparative Example 2:

[0106] A self-compacting concrete using waste slag as raw material. Different from Example 5, no lanthanum oxide / carbon composite material is added to the self-compacting concrete.

[0107] Performance Test:

[0108] 1. Test expansion and 28d chloride ion diffusion coefficient

[0109] The self-compacting concrete prepared in Examples 5-10 and Comparative Examples 1-2 was tested for expansion according to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", and tested for 28d chloride ion diffusion coefficient according to JTG / T B07-01-2006 "Technical Specifications for Anticorrosion of Concrete Structures in Highway Engineering". The specific test results are shown in Table 1.

[0110] Table 1 Test results of expansion degree and 28d chloride ion diffusion coefficient

[0111]

[0112]

[0113] As shown in Table 1, the self-compacting concrete prepared in Examples 5-10 of the present invention has good fluidity and a low 28d chloride ion diffusion coefficient. By comparing Example 5 with Comparative Examples 1-2, it can be seen that modifying the waste residue and adding lanthanum oxide / carbon composite materials can improve the fluidity of the concrete to a certain extent and reduce the 28d chloride ion diffusion coefficient, especially the addition of lanthanum oxide / carbon composite materials can significantly reduce the 28d chloride ion diffusion coefficient of the concrete, so that the construction performance and corrosion resistance of the self-compacting concrete are improved.

[0114] 2. Test compressive strength and flexural strength

[0115] The self-compacting concrete prepared in Examples 5-10 and Comparative Examples 1-2 was made into 100mm×100mm×100mm test blocks, placed in a standard curing room for curing, and the compressive strength and flexural strength of the test blocks were tested at 3d and 28d. The test method was based on GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The specific test results are shown in Table 2.

[0116] Table 2 Compressive strength and flexural strength test results

[0117]

[0118] As shown in Table 2, the concrete test blocks prepared in Examples 5-10 of the present invention have excellent compressive strength and flexural strength, and have high strength and toughness. At the same time, by comparing Example 5 with Comparative Examples 1-2, it can be seen that after the waste residue is modified, the compressive strength of the self-compacting concrete can be enhanced, and the flexural strength can be improved to a certain extent, and the addition of lanthanum oxide / carbon composite materials can significantly enhance the compressive strength and flexural strength of the self-compacting concrete.

[0119] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A self-compacting concrete using waste slag as raw material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of silicate cement, 115-145 parts of modified waste residue, 65-85 parts of river sand, 230-260 parts of crushed stone, 2.6-3.7 parts of lanthanum oxide / carbon composite material, 1.2-1.5 parts of mullite fiber, 2.3-4.2 parts of EVA emulsion, 3-6 parts of silica fume, 0.3-0.6 parts of water reducer and 45-53 parts of water; The modified waste residue is prepared by the following method: (1) Evenly mix iron tailings, gold tailings and building stone tailings to obtain mixed waste slag; (2) placing the mixed waste residue in a formic acid aqueous solution so that the formic acid aqueous solution submerges the mixed waste residue, then heating the mixture to 50-55° C., stirring the mixture, and filtering the mixture to obtain pretreated mixed waste residue; (3) placing the pretreated mixed waste residue and the maleic anhydride aqueous solution in a tank body, so that the maleic anhydride aqueous solution submerges the pretreated mixed waste residue, and then sealing the tank body, and raising the temperature inside the tank body to 70-75° C., after standing, opening the tank body and filtering to obtain modified waste residue; The lanthanum oxide / carbon composite material is prepared by the following method: 1) adding lanthanum nitrate hexahydrate, polyvinyl pyrrolidone, polyethylene glycol and trimesic acid to a mixed solvent to obtain a mixed solution; placing the mixed solution in a reaction kettle, then sealing the reaction kettle, placing it in an oven, then heating it to 150-170° C. for solvent thermal reaction for 10-12 hours, then cooling it to room temperature, opening the reaction kettle, centrifugally washing the material in the kettle, and then vacuum drying it to obtain a solid intermediate product; 2) grinding the solid intermediate product and passing it through a 100-150 mesh sieve, then heating it to 260-280° C. in an argon atmosphere, keeping it warm for 30-50 minutes, then heating it to 760-800° C. in an argon atmosphere, keeping it warm for 70-100 minutes, then cooling it to room temperature in an argon atmosphere, grinding it and passing it through a 200-300 mesh sieve to obtain a lanthanum oxide / carbon composite material; The mass ratio of the mixed solvent, lanthanum nitrate hexahydrate, polyvinyl pyrrolidone, polyethylene glycol and trimesic acid is (500-600): (1-1.5): (16-24): (3-5): (2.5-4).

2. The self-compacting concrete using waste slag as raw material according to claim 1, characterized in that: In step (1), the mass ratio of the iron tailings, gold tailings and building stone tailings is 10:(2-6):(1-3); The fineness modulus of the iron tailings is 0.8-1.3; the fineness modulus of the gold tailings is 0.5-0.7; the particle size of the building stone tailings is 0.2-3mm, and the stone powder content is 15-25%.

3. The self-compacting concrete using waste residue as raw material according to claim 1, characterized in that: In step (2), the mass fraction of the formic acid aqueous solution is 2-3%; and the stirring time is 30-50 min.

4. The self-compacting concrete using waste slag as raw material according to claim 1, characterized in that: In step (3), the mass fraction of the maleic anhydride aqueous solution is 0.3-0.5%, and the standing time is 60-80 minutes.

5. The self-compacting concrete using waste slag as raw material according to claim 1, characterized in that: In step 1), the mixed solvent is prepared by mixing water, ethanol, and N,N-dimethylformamide in a volume ratio of 1:(2-3):(1-2); The number average molecular weight of the polyvinyl pyrrolidone is 50000-80000; the polyethylene glycol is polyethylene glycol 400 or polyethylene glycol 600.

6. The self-compacting concrete using waste residue as raw material according to claim 1, characterized in that: In step 2), the temperature is increased to 260-280°C at a rate of 2-3.5°C / min; and the temperature is increased to 760-800°C at a rate of 4.5-7°C / min.

7. The self-compacting concrete using waste residue as raw material according to claim 1, characterized in that: The silicate cement is P.II 52.5 silicate cement; The river sand is medium sand in zone II, with a fineness modulus of 2.4-2.8; The crushed stone is a continuous grade crushed stone with a particle size of 5-20 mm; The diameter of the mullite fiber is in the range of 100-500 μm, and the aspect ratio is 8-15; The solid content of the EVA emulsion is 65-70%; The silica content of the silica fume is more than 90%, and the specific surface area is 17000-20000m 2 / kg; The water reducing agent is a powdered polycarboxylate water reducing agent.

8. The method for preparing self-compacting concrete using waste slag as raw material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Add EVA emulsion to the modified waste residue and stir for 10-15 minutes, then add river sand and stir evenly, then add lanthanum oxide / carbon composite material and stir evenly, then add mullite fiber and silica fume in sequence, stir evenly, and obtain a mixture; Step 2: Add the mixture to the silicate cement, stir evenly, then add 2 / 3-4 / 5 of the formula amount of water, stir for 100-130 seconds, then add the remaining raw materials, stir evenly to obtain the self-compacting concrete.

Citation Information

Patent Citations

  • C60 high-performance self-compacting concrete suitable for arched structure and preparation method thereof

    CN115536340A

  • Anti-crack corrosion-resistant concrete admixture as well as preparation and application of anti-crack corrosion-resistant concrete admixture

    CN106698992A

  • Preparation method of high-content iron tailing sand self-compacting concrete

    CN112456916A